ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA MA DI KABUPATEN BANDUNG BARAT PADA MATERI BARISAN DAN DERET - Ayu Dwi Putri; Anik Yuliani (Journal on Education, 2019)
This article is an analysis of test questions about High School class XI mathematical reasoning abilities. This analysis was conducted aimed at knowing and recognizing the types of difficulties experienced by students and for determining the level of mathematical reasoning of High School students in West Bandung Regency. This research is a qualitative descriptive study. A total of 34 High School students in class XI were used as samples. Instruments to test mathematical reasoning abilities are given as many as 5 items with line and series material in the form of description. Processing data in this study using Microsoft Excel and SPSS. V.23. The results of the study obtained based on the written tests conducted were the mathematical reasoning abilities of High School students in West Bandung District who had mathematical reasoning that was still low.